SAT0484 Incidence of tuberculosis, serious infections, and lymphoma in patients with rheumatoid arthritis who received biologics and non-biologic treatment in taiwan. (23rd January 2014) - Chiu, Y.M.; Lang, H.C.; Lin, H.Y.; Yang, M.T.; Fang, C.; Lai, C.; Tang, B.
Abstract : Background: The risk of tuberculosis (TB), infection and lymphoma is a major concern for anti-tumor necrosis factor (anti-TNF) therapies. However, limited comparative data about the rates in Asia and Taiwan Objectives: To assess the incidence of TB, serious bacterial infection and lymphoma in rheumatoid arthritis patients who received anti-TNF therapy and non-biologic treatment in Taiwan. Methods: The National Health Insurance Research Database (NHIRD) 1999-2009 data were analyzed. NHIRD comprises longitudinal patient-level data which covers long-term disease tracking on almost 99.9% of population in Taiwan. Adult patients (age ≥18) have at least twice diagnosis of RA (ICD-9 "714.0x") and hold catastrophic illness card who received traditional disease-modified anti-rheumatic drug (TDMARDs) or BDMARDs (including etanercept, adalimumab or rituximab were included in the analysis. Patients with prior TB, serious infections or lymphoma were excluded. Patients who received TDMARDs were matched with BDMARDs cohort with 2:1 ratio using propensity score method to adjust age, gender, disease severity, and co-morbidities. Incidence rates of TB, serious infection and lymphoma were defined as number of events divided by total patient exposure years. Incidence rate ratios (IRRs) were calculated between patients on TDMARDs vs. BDMARDs, and among different BDMARDs. Results: Of total patients in between 1999 and 2009, 35, 589 met the inclusion criteria, and were included in the analysis. The average duration of RA was 8.2 years; 79.1% was female, and the average age was 60.6 years. Patients on BDMARDs group had higher incidences of TB, serious infections and lymphoma compared with patients who received TDMARDs only (Table 1 ). Within BDMARDs group, 3, 335 patients (75.8%) and 1, 029 patients (23.2%) and had ever received first line treatment of etanercept and adalimumab respectively. Patients on etanercept group had lower incidences of TB, serious infections and lymphoma compared with patients on adalimumab group. All the differences were statistically significant (Table). Moreover, adalimumab group had TB or serious infections significantly earlier than etanercept group after BDMARD treatment. Conclusions: Although BDMARD increases the risks of TB, infections and lymphoma, risks were not equal among different BDMARDs. Patients who receiving Etanercept had lower risks developing these adverse events compared with patients who receiving adalimumab. References: Taiwan Drug Relief Foundation & ADR Reporting Center's signal detection, 2011. Lau CS, et al, Nat Clin Pract Rheumatology. 2007;3:119. Tang B, et al, Arthritis & Rheumatism Vol. 63, No. 10 (Supplement), October 2011. Disclosure of Interest: Y. M. Chiu Grant/Research support from: Pfizer Inc., H. C. Lang Grant/Research support from: Pfizer Inc., H. Y. Lin Grant/Research support from: Pfizer Inc., M. T. Yang Grant/Research support from: Pfizer Inc., C. Fang Grant/Research support from: Pfizer Inc., C. Lai Grant/Research support from: Pfizer Inc., B. Tang Grant/Research support from: Pfizer Inc.